1999
DOI: 10.1017/s0890037x00042214
|View full text |Cite
|
Sign up to set email alerts
|

Response of Peanut (Arachis hypogaea) and Selected Weeds to Diclosulam

Abstract: Field studies were conducted at five locations in North Carolina and Virginia during 1996 and 1997 to evaluate weed control, peanut (Arachis hypogaea) response, and peanut yield following diclosulam applied preplant incorporated (PPI) and in systems with commercial herbicide standards. All plots received a PPI treatment of ethalfluralin at 840 g ai/ha. Ethalfluralin plus diclosulam controlled entireleaf morningglory (Ipomoea hederaceavar.integriuscula), ivyleaf morningglory (I. hederacea), pitted morningglory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 10 publications
(10 reference statements)
4
39
0
Order By: Relevance
“…Paraquat ϩ bentazon EPOST, either alone or fb chlorimuron provided less than 80% control; however, all other treatments evaluated provided at least 89% control in 2003 (Table 4). In previous research, diclosulam and flumioxazin PRE, chlorimuron, imazapic, pyridate, and 2,4-DB POST controlled ivyleaf morningglory 70 to 100% (Bailey and Wilcut 2002;Bailey et al 1999aBailey et al , 1999bEdenfield et al 2001;Taylor-Lovell et al 2002). No differences were observed between peanut planting patterns for ivyleaf morningglory control (Table 4).…”
Section: Resultsmentioning
confidence: 68%
“…Paraquat ϩ bentazon EPOST, either alone or fb chlorimuron provided less than 80% control; however, all other treatments evaluated provided at least 89% control in 2003 (Table 4). In previous research, diclosulam and flumioxazin PRE, chlorimuron, imazapic, pyridate, and 2,4-DB POST controlled ivyleaf morningglory 70 to 100% (Bailey and Wilcut 2002;Bailey et al 1999aBailey et al , 1999bEdenfield et al 2001;Taylor-Lovell et al 2002). No differences were observed between peanut planting patterns for ivyleaf morningglory control (Table 4).…”
Section: Resultsmentioning
confidence: 68%
“…None ofthe cultivars evaluated were negatively impacted « 5% visual injury and no yield reduction) by either imazapic or diclosulam applied at twice the labeled rate in any of the 3 yr of the study (data not shown). Previous research has indicated similar results (no effect on peanut yield) with diclosulam applied to virginia-type cultivars (Wilcut et al, 1997;Bailey et al, 1999Bailey et al, , 2000. Others have evaluated imazapic on viginia-, spanish-, and runner-type cultivars Wilcut et al, 1996;Dotray et al, 2001).…”
Section: Nonementioning
confidence: 88%
“…Ipomoea hederacea is a self-compatible annual vine that is believed to have a mixed mating system (Ennos, 1981;Elmore, 1986) due to its ability to produce viable seeds from autogamous fertilizations and hand outcrosses. This species is frequently found in cultivated gardens and disturbed areas and is a serious pest species in agricultural crops such as soybean (Thullen and Keeley, 1983;Klingaman and Oliver, 1996), cotton (Klingaman and Oliver, 1994), and peanuts (Bailey et al, 1999) throughout the southeastern United States. Germination occurs between mid-May and August, and flowering in east-central Alabama (AL) begins in early August.…”
mentioning
confidence: 99%